Optimization of Debtor Protection in Problems Misbruik van omstandigheden What Creditors Do in The Execution of Viat Parate on Collateral Items - Tanjung, Silva Fawjiah (Jurnal Konstatering, 2023)
The existence of HT agreements often creates opportunities Misbruik van omstandighedenor misuse of circumstances that often harm the debtor as a powerless party due to a low bargaining position, because the debtor is a party that needs loan funds from the creditor, one of which is in the execution of parate collateral objects. This article aims to analyze the urgency of debtor protection from Misbruik van omstandigheden which is carried out by creditors in the implementation of parate HT executions. The method used in this paper is normative juridical. Based on the analysis conducted, it can be seen that Article 6 and Article 20 of the UUHT, which are also supported by Article 1178 paragraph (2) of the Civil Code, have resulted in loopholes for misuse of circumstances or misbruik van omstandigheden by creditors against debtors in terms of implementing agreements related to the execution of mortgage collateral objects. separately. Keywords: Agreement; Creditor; Debtor.